Quantifying intensity - Brandon, R.
Target intensity for health benefits = 40% VO2 max = 63% HR max Target intensity for aerobic fitness = 60-80% VO2max = 75-88% HR max Target intensity for elite training = >85% VO2max = >92% HR max Swain et al equation: % HR max = 0.64 x % VO2 max + 37 Miller et al formula: HR max = 217 - (0.85 x age)